To what extent is child-to-parent violence bi-directional? - Ibabe, Izaskun; Jaureguizar, Joana (Anales de Psicología / Annals of Psychology, 2011)
Child-to-parent violence is a family problem that has remained obscured for decades. The main purpose of this study was to explore gender differences in victims and perpetrators of child-to-parent violence. The importance of intra-family violence in the development of this type of violent behavior was also studied. The sample comprised 485 adolescents from the province of Gipuzkoa (Spain), of both sexes, taken from 9 schools and aged 12 to 18. As found in many previous studies, sons were more likely to be perpetrators of physical abuse than daughters. Although mothers suffered more psychological and emotional abuse than fathers, there were no differences between mothers and fathers with regard to physical abuse from their children. The hypothesis of the bi-directionality of violence was confirmed for physical violence in the male group that battered their parents. Similarly, marital violence (violence between par-ents) was a predictor of the three types of child-to-parent abusive behav-iours (physical, psychological and emotional) for the male group. Moreo-ver, we found three psychological variables in adolescents (drug abuse, self-esteem and anxiety) that emerged as predictors of child-to-parent violence.